2020
DOI: 10.3389/fpls.2020.582011
|View full text |Cite
|
Sign up to set email alerts
|

Potential, Challenges, and Threats for the Application of New Breeding Techniques by the Private Plant Breeding Sector in the EU

Abstract: Reconciling sustainability with agricultural productivity in the face of climate change relies strongly on the development of resilient, high-yielding crops of superior nutritional value that can be grown more resource efficiently. Therefore, innovation in plant breeding has gained unprecedented importance. Plant breeding depends upon genetic variability within crops and their relatives as a basis for developing new plant varieties with improved characteristics. Plant breeders are continuously integrating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Several of these aims would further fit within the economic interest, especially of the biotechnology and breeding sectors in the expansion and facilitation of product development based on NGT applications, which have been previously documented [153]. In our study, identified aims and expectations generally tend to derive from the socio-political field and are only loosely connected with economic interests.…”
Section: Discussionmentioning
confidence: 67%
“…Several of these aims would further fit within the economic interest, especially of the biotechnology and breeding sectors in the expansion and facilitation of product development based on NGT applications, which have been previously documented [153]. In our study, identified aims and expectations generally tend to derive from the socio-political field and are only loosely connected with economic interests.…”
Section: Discussionmentioning
confidence: 67%
“…The novelty and value of genomic editing in applied breeding has largely recognized. Nevertheless, before such technology could be fully implemented and largely produce practical results, it will be important that a science-based regulatory frame be applied consistently worldwide [147][148][149][150][151].…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of plant breeding companies in the EU, this was shown to be the case irrespective of the size of the enterprise, with larger developers relocating research and development programs to jurisdictions with more enabling regulatory environments. This refocus to non-EU markets may not be feasible for SMEs with markets predominantly in the EU, who reported discontinuing, modifying or postponing research and development programs that involved the use of genome editing tools ( Jorasch, 2020 ). These issues appear to extend to less politicised jurisdictions where some regulatory clarity has been provided.…”
Section: Regulatory Pathway For Crops Developed Using Genome Editingmentioning
confidence: 99%
“…The scientific literature strongly emphasises the features of ease and speed for trait and crop improvement using genome editing, with estimates for halving the development process, e.g., from 8 to 10 years with conventional tools, 8–12 years if transgenic tools are also used, and 4–6 years with the use of genome editing ( Chen et al, 2019 ). Genome editing tools are expected to be widely implemented in plant breeding and to complement existing breeding processes ( Jorasch, 2020 ; Gao, 2021 ).…”
Section: Introductionmentioning
confidence: 99%